2017
DOI: 10.3892/mmr.2017.7335
|View full text |Cite
|
Sign up to set email alerts
|

Conditioned medium from tonsil-derived mesenchymal stem cells promotes adiponectin production

Abstract: Mesenchymal stem cells (MSCs) are often considered to be a good source for the development of regenerative medicine. Previously, we reported that tonsil‑derived MSC conditioned medium (T‑MSC CM) produces visceral fat reducing effects. As reduced visceral adiposity is closely associated with an increase in circulating adiponectin, the present study investigated the effects of T‑MSC CM on adiponectin production. T‑MSC CM was collected from previously isolated and characterized T‑MSCs and injected into senescence… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 34 publications
0
3
0
Order By: Relevance
“…In contrast to the osteogenic TMSCs, there are few studies looking at possible applications of adipogenically differentiated TMSCs, probably due to the lack of translational and clinical applications. However, in one study of interest, CM from adipogenically differentiated TMSCs was injected into mice and produced a decrease in body fat mass and subsequent weight loss . The same study also determined that injected TMSCs probably stimulated adipose tissues of mice to increase the production of adiponectin, which triggers redistribution of body fat , eventually leading to weight loss.…”
Section: Tonsil‐derived Mscs (Tmscs)mentioning
confidence: 99%
“…In contrast to the osteogenic TMSCs, there are few studies looking at possible applications of adipogenically differentiated TMSCs, probably due to the lack of translational and clinical applications. However, in one study of interest, CM from adipogenically differentiated TMSCs was injected into mice and produced a decrease in body fat mass and subsequent weight loss . The same study also determined that injected TMSCs probably stimulated adipose tissues of mice to increase the production of adiponectin, which triggers redistribution of body fat , eventually leading to weight loss.…”
Section: Tonsil‐derived Mscs (Tmscs)mentioning
confidence: 99%
“…Intriguingly, MSC therapy could alleviate adipose tissue inflammation and rebalance serum adipokine levels. Indeed, injection of conditioned media from tonsil-derived MSC was reported to increase the expression of adiponectin in epididymal adipose tissue, as well as circulating levels of total and high-molecular-weight adiponectin in obese mice 94 . Similarly, treatment with BM-MSC or their conditioned media increased adiponectin gene expression in HFD-fed mice, which was accompanied by protection against obesity-induced cardiac dysfunction 95 .…”
Section: Msc Therapy: a Promising Strategy For Normalization Of Adipo...mentioning
confidence: 99%
“…Likewise, our research group found that injecting MSCs isolated from human palatine tonsils (T-MSCs) reduces high-fat diet-induced weight gain in mice [ 14 ]. We also found that conditioned medium (CM) from T-MSCs inhibits adipocyte differentiation and reduces weight gain in senescence-accelerated mouse prone 6 (SAMP6) mice, which exhibit obesity in aging [ 15 , 16 ]. To extend these previous observations, we aimed to elucidate the mechanisms by which T-MSC CM inhibits adipocyte differentiation.…”
Section: Introductionmentioning
confidence: 99%